Patients with severe liver cirrhosis followed up by L-[1-^ C] phenylalanine breath test - Ishii, Yukimoto; Suzuki, Shigeru; Kohno, Tomohisa; Aoki, Masaru; Goto, Iori; Kohno, Tadashi; Ito, Asuka; Asai, Satoshi (Journal of gastroenterology, 2003)
Compared to healthy subjects, patients with severe liver cirrhosis (LC) are reported to show lower values in the L-[1-(13)C] phenylalanine breath test (PBT). We performed this test several times during the clinical course in two patients with severe liver cirrhosis (LC). Patient 1 was a 67-year-old woman with non-B, non-C LC and hepatocellular carcinoma (HCC) in the lateral hepatic segment. Because the patient wanted to receive nonsurgical treatment for HCC, intraarterial administration of zinostatin stimalamer was performed. The patient was hospitalized four times before her death from liver failure on December 20, 2000. During her clinical course, PBT was performed four times. Values for both the rate of hepatic phenylalanine oxidation (%(13)C dose h(-1)) and %(13)C cumulative excretion gradually decreased during her clinical course. Patient 2 was a 57-year-old man with hepatitis C virus (HCV)-positive LC. He was hospitalized seven times between December 1998 and his death on May 24, 2001. During his clinical course, PBT was performed four times. Values for both %(13)C dose h(-1) and %(13)C cumulative excretion decreased during his clinical course. We confirmed that PBT was useful for following the course of LC.